(untitled) (Global Journal of Management and Business Research, 2022)
The study aims to identify bibliometric characteristics of articles published between 2010 and 2019 on accounting expertise using the Scientific Periodicals Electronic Library (SPELL) database. The methodology used in the research is characterized as a bibliometric, descriptive and qualitative research. The data were collected from that database, where 17 articles were found that contained the keyword "PeríciaContábil", which were produced by 49 authors, most of whom were co-authored by two authors from the Midwest region of the city of Brasília-DF and of the teaching institution UniversidadeCatólica de Brasília (UCB). The articles are distributed in 12 magazines and there is practically no publication in those considered to be of high impact, having as the most discussed subject: general aspects of accounting expertise, despite the importance of this area of practice of the accounting professional, there are few publications on the subject. It is suggested, therefore, that future research will be developed on the theme "accounting expertise".